Hubungan Komponen Perilaku Pekerja Pengelasan terhadap Pengunaan Alat Pelindung Diri pada Pekerja Pengelasan di PT. Industri Kapal Indonesia (Persero) Makassar, Sulawesi Selatan - Krisdayanti; Uswantun Hasanah; Andi Alim; Verawati (Journal of Health (JoH), 2023)
Personal Protective Equipment (PPE) is a set of tools used by workers to protect all or part of their body against the possibility of potential work accident hazards in the work area. The use of PPE is often considered insignificant or trivial, but the discipline of workers in using PPE is still low, so the risk of work accidents that can endanger workers is quite large. The purpose of this study was to determine the relationship between knowledge, attitudes and actions of using PPE for workers at PT. Indonesian Ship Industry (Persero) Makassar District of Tallo, Makassar City, South Sulawesi Province. The type of research used is analytic research with a total sample of 49 people. The results showed that there was a relationship between knowledge and PPE users (p=0.05), there was a relationship between attitude and use of PPE (p=0.01), and there was a relationship between action and use of PPE (p=0.03). Based on the results of the study it can be concluded that there is a relationship between knowledge, attitudes and actions of using PPE in welding workers. It is suggested to workers to always behave properly by using PPE properly. Do not use half-time PPE or if there is only a supervisor because if a work accident occurs, the losses will return to the respective workers. Accidents can result in permanent disability or loss of a limb.